2011
DOI: 10.1016/j.ijthermalsci.2010.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of non-uniform heating effect on flow boiling instabilities in a microchannel-based heat sink

Abstract: Copyright @ 2011 ElsevierTwo-phase flow boiling in microchannels is one of the most promising cooling technologies for coping with high heat fluxes produced by the next generation of central processor units (CPUs). If flow boiling is to be used as a thermal management method for high heat flux electronics it is necessary to understand the behaviour of a non-uniform heat distribution, which is typically the case observed in a real operating CPU. The work presented is an experimental study of two-phase boiling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 15 publications
(18 reference statements)
0
15
0
2
Order By: Relevance
“…For uniformly heated parallel channels, Qu, Mudawar [14] defined two forms of reversal, Mode 1: coordinated (low frequency) and Mode 2: uncoordinated (high frequency). Bogojevic et al [15] deduced similar behaviour in a group of 40 channels with axially non-uniform heating and uneven flow distribution between channels detected by wall temperature sensors spanning 3 groups of 7 channels. At low heat flux, some channels had subcooled wall temperatures indicating single-phase flow, others were superheated, indicating boiling.…”
Section: Inlet Flow Reversal and Upstream Compressibilitymentioning
confidence: 71%
See 2 more Smart Citations
“…For uniformly heated parallel channels, Qu, Mudawar [14] defined two forms of reversal, Mode 1: coordinated (low frequency) and Mode 2: uncoordinated (high frequency). Bogojevic et al [15] deduced similar behaviour in a group of 40 channels with axially non-uniform heating and uneven flow distribution between channels detected by wall temperature sensors spanning 3 groups of 7 channels. At low heat flux, some channels had subcooled wall temperatures indicating single-phase flow, others were superheated, indicating boiling.…”
Section: Inlet Flow Reversal and Upstream Compressibilitymentioning
confidence: 71%
“…It is often assumed that the downstream compressibility is infinite, so that the exit pressure is maintained constant by a condenser or open discharge to the atmosphere. Measurements as in Bogojevic et al [15], suggest that fluctuations in the outlet pressure may be of similar magnitude to those in the inlet pressure in a closed system or in an open system with two-phase flow in a long discharge pipe to the atmosphere.…”
Section: Inlet Flow Reversal and Upstream Compressibilitymentioning
confidence: 83%
See 1 more Smart Citation
“…Bogojevic et al [65] investigated experimentally the effects of nonuniform heating on flow boiling instabilities in microchannel-based heat sink using water as the cooling liquid. The results indicate that the onset of boiling caused metastable non-uniform flow distribution, with boiling in some channels and single-phase flow in others, leading to transverse variations in temperature that were less severe when the hotspot was at the downstream position.…”
Section: Experimental Studies On MCmentioning
confidence: 99%
“…They found that the flow regime and the type of two-phase flow instabilities depended on the q/G ratio and the inlet subcooling conditions. Bogojevic et al [23] also presented an experimental study on the system instability in microchannels with non-uniform heating. They studied the effect of the hotspot location on pressure drop and the temperature profile and found that a system with axially non-uniform heating leads to a high temperature non-uniformity in the transverse direction.…”
Section: Introductionmentioning
confidence: 99%